Status of the linear accelerator-injector at the TNK facility - Anchugov, O.V.; Chernov, K.N.; Filiptchenko, A.V.; Gudkov, B.A.; Kokin, E.N.; Matyash, N.V.; Medvedko, A.S.; Ostreiko, G.N.; Ruvinsky, S.I.; Serdobintsev, G.V.; Ushakov, V.A. (Вопросы атомной науки и техники, 2008)
In 2006, the work was continued at the linear accelerator-injector of TNK facility, Zelenograd. In November-December, the linear accelerator conditioning was carried out to increase the output electron energy. The accelerated electron beam was obtained at the Faraday's cup located in the plane which was equivalent to the booster ring entrance point. The paper presents the accelerating structure conditioning results and diagrams of the beam pulse shape at the accelerator output and energy spectrum at the booster ring input.